The prevalence and severity of the symptom burden in patients with End Stage Renal Disease (ESRD) in a resource limited setting - Van Vuuren, Ane Jansen (Department of Medicine, 2025)
Globally, kidney failure is Increasing. In South Africa, limited access to kidney replacement therapy (KRT) necessitates urgent improvement in kidney supportive and palliative care. Methods: This prospective, cross-sectional, mixed-method study was conducted at two Cape Town hospitals from June 2021 to June 2023. Participants with end-stage kidney failure (n=75) were categorized into three groups: receiving dialysis, on the waiting list, and ineligible for state-funded KRT (category 3). Data collection included demographics, comorbidities, and social circumstances. The Integrated Palliative care Outcome Scale Renal (IPOS-Renal) questionnaire assessed symptom burden, complemented by qualitative insights from open-ended interviews, which underwent thematic analysis. Results: The cohort was young, with a median age of 40 (33-45) years, and faced significant poverty, commonly experiencing weakness/lack of energy (64%). Patients on the waiting list and those in category 3 had a higher symptom burden. Category 3 patients had the highest prevalence of shortness of breath (p=0.006), dry mouth (p<0.001), poor mobility (p=0.007), and restless legs (p=0.038). Emotional symptoms were prevalent across all groups. Category 3 patients experienced the most severe physical symptoms, including shortness of breath (p=0.003), sore/dry mouth (p<0.001), drowsiness (p=0.028), and poor mobility (p<0.001). They also experienced the highest levels of personal anxiety (p<0.001), patient perception of family anxiety (p=0.037), and appointment time wastage (p=0.021). Qualitative findings highlighted concerns for families, fears about unfulfilled lives, and the need for better access to information. Conclusion: Limited literature exists on symptom burden in conservative kidney care with dialysis rationing. Recommendations advocate early multidisciplinary team involvement, improved patient and family support, and enhanced palliative care training.